(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Technically, the primary objective of the advertising text is to handle behavioral scenarios and motivations of consumers. Hence, this present study makes an attempt to describe the outcomes of observations and a research to evaluate the perception of several advertising texts’ titles and headings. This survey involves twelve subjects, in which utilizing Pupil eyewear glasses and software from Pupil (Germany), the participants take a look at six various headings oriented to the right or left hemisphere of the brain. Based on the outcomes of analyzing the observations outcomes, the likelihood of boosting the attractiveness of the titles and headings via the utilization of syntax concentrated upon the preferential activation of a cerebral hemispheres wasn’t approved. Conclusions are made over the desirability of utilizing brief exclamation or unallocated sorts of promotional suggestions.